An interactive e-book development based on green chemistry study on Hydrocarbon. Issue 1 (May 2021) - Anwar, M; Alimin,; Munawwarah,
Abstract: The aim of this study is to make an interactive e-book based on the green chemistry approach. This interactive e-book was prepared by using the development rearch method by Richey, Klein, and Nelson with the DDE model (Design, Development, and Evaluation). Interactive aspects of this teaching material are the "watch for know" coloumn that presents related learning videos, links that contain related general knowledge, practice questions and competency test at the end of learning activities that consist of questions, scores, and the answer key. This interactive e-book includes green chemistry aspect as an approach by providing contextual cases in hydrokarbon subject. This interactive e-book is valid after going through two types of validation, that were content and media validation. There are two validator in each type of validation. The validation questionnaire is an instrument used in this study. The content validation questionnaire consist of subject accuracy, recency, and communication aspect. The media valiodation questionnaire consist of media design and navigation/operation.